Organic zinc absorption by the intestine of broilers in vivo. Issue 8 (22nd May 2017) - Yu, Yu; Lu, Lin; Li, Su-Fen; Zhang, Li-Yang; Luo, Xu-Gang
Abstract: In Expt 1, a Zn-unsupplemented basal diet (control) and the basal diet supplemented with one of four different Zn sources, including ZnSO4, Zn-amino acid chelate with a weak chelation strength (Zn-AA W), Zn-protein chelate with a moderate chelation strength (Zn-Pro M) and Zn-protein chelate with a strong chelation strength (Zn-Pro S) were fed to broiler chickens from days 14 to 28. On day 28, Zn content in plasma from the hepatic portal vein increased ( P <0·05) in the following order: control4 <Zn-AA W<Zn-Pro M<Zn-Pro S. Meanwhile, metallothionein (MT) mRNA levels in the duodenum, jejunum and ileum were enhanced ( P <0·05) by Zn addition regardless of Zn source. However, no differences among different Zn sources were observed. In Expt 2, ligated duodenal loops from Zn-deficient broilers (28-d old) were perfused with solutions containing 0–2·464 mmol Zn/l from the above-mentioned four Zn sources for up to 30 min. The uptake kinetics of Zn followed a saturable carrier-mediated process. The maximum absorption velocity values were in the following order: control4 <Zn-AA W<Zn-Pro M<Zn-Pro S. Moreover, MT mRNA levels for Zn-Pro S ( P <0·03), Zn-Pro M ( P >0·05) and Zn-AA W( P <0·04) were higher than those for ZnSO4 . These findings indicate that organic Zn absorption (especially Zn-Pro S) in intact living broilers was more effective than that of inorganic Zn; organic Zn absorption in the ligated duodenal segment was a saturable carrier-mediated process similar to that of ZnSO4 . Moreover, except for MT, there might be other Zn transporters involved in Zn absorption that are affected by different Zn sources.